Efek ekstrak etanol biji adas (Foeniculum vulgare Mill.) pada berbagai dosis terhadap produksi susu tikus laktasi dan pertambahan berat anak tikus - Khoiriyah, Nur; Kustiyah, Lilik; Roosita, Katrin (Poltekkes Kemenkes Aceh, 2025)
Background: Breastfeeding is highly recommended to support infant growth and development. However, exclusive breastfeeding rates remain at 55,5%. One contributing factor is low milk production. Fennel seeds are one ingredient thought to increase milk production.Objectives: This study aimed to analyze the phytochemical content and effects of ethanol extract of fennel seeds on milk production and pup weight gain.Methods: This animal study was conducted from March to September 2019. Animal maintenance was carried out at Biopharmaceutical Study Center, Bogor. A total of 24 lactating rats were grouped into four treatments (EA1:88,75 mg/kg, EA2:177,50 mg/kg, EA3:355,00 mg/kg, and N:control). The interventions were administered from day 3 to 21 of lactation. Data included phytochemical, milk production, and pup weight gain. The milk production was calculated indirectly based on the pup weight gain. Data were analyzed using ANOVA at α=0.05.Results: Extract of fennel seed contains flavonoids, phenols, tannins, saponins, and steroids. Milk production up to day 15 of lactation in N, EA1, EA2, and EA3 was 1,65 g/day, 2,67 g/day, 2,34 g/day, and 1,95 g/day, respectively. Up to day 15, there was a significant difference in milk production in EA1 compared to the control (p=0,047). However, milk production up to day 21 of lactation showed no significant difference (p=0,055). Pup weight gain was also not significantly different (p>0,05).Conclusion: Administration of EA1 significantly increased milk production up to day 15 compared to the control, but milk production up to day 21 and the pup weight gain showed no significant results.